Extraction and Partial Purification of Lipopolysaccharide from Clinical Proteus mirabilis Isolate and Compared with Standard Bacteria - Zuhir , Rawnaq; Alaubydi , Mouruj A. Sattar (Iraqi Journal of Science, 2022)
Ninety five samples were collected from different samples (urine, ear and wounds swaps), from hospitals in Baghdad city. The results of cultural, microscopic , biochemical tests indicated that in urine samples E.coli have high occurrence frequency 19 (47.5%) followed by Proteus mirabilis 18(45%) and Klebsiella species 1 (2.5%), while in wounds samples each of Pseudomonas spp. and Proteus mirabilis 10 (25%) , then followed by E.coli with 5 (12.5%) and Klebsiella species 3 (7.5%). Ear swaps samples revealed that Pseudomonas aeruginosa 7 (46%) was the major bacterium followed by Proteus mirabilis 4(26.6).Sensitivity test against eleven antimicrobial agents was done for all of the Proteus mirabilis isolates (32 isolates). The results displayed that most of the isolates were resistant to Methicillin (96.8%), and Rifampin (93.7%) followed by trimethoprim–sulfamethoxazole (71.8%), chloramphenicol (62.5%), and cefazoline (59.3%). while the most effective antimicrobial agents against P. mirabilis were Imipenem (96.9%), Azetronam (81.3%), Azithromycin (71.9%) ,Ciprofloxacin (69%).Whereas a moderate effect appeared against both gentamycin and tobramycin in a percentage of (53.2 and 62.5) % respectively. More resistant isolate was selected, and lipopolysaccharide was extracted by hot EDTA method and the yield was (051) mg LPS from (22)g dry weight cell of pathogenic P.mirabilis and (95) mg as LPS from (16) g dry weight cell of standard bacteria were obtained. After partial purification ,chemical analysis of crud and partial purified LPS showed that the carbohydrate percentages were (35 , 44.3) % and (49 , 62)%, while the protein percentage (0.98 ,0.1) % and ( 1.3 ,0.1)% for the standard and isolated bacteria respectively ,whereas both extract appeared free from nucleic acid . Molecular weight of LPS was estimated and it was equivalent to (63095 and 70794) Dalton for the standard bacteria and pathogenic one respectively.